Hydrostatic compression tests, capillary rheometry tests, and extrusion tests performed on unvulcanized rubber confirm importance of compressibility for die swell — Arguments from dimensional analysis. (September 2021) - Plachy, R.; Hellmich, C.; Arthofer, F.; Robin, S.; Holzner, A.; Scheiner, S.
Abstract: This paper aims at elucidating which factors are effective in terms of influencing the die swell of unvulcanized rubber upon extrusion. To that end, compression, viscosity, and extrusion tests were performed on two types of ethylene–propylene–diene rubbers, while additional compression tests were performed on natural rubber. First, all three testing modalities were assessed separately, revealing that for the tested materials the compressibility is pressure-dependent; the viscosity is velocity-dependent; and the die swell is influenced by several, partly intertwined factors. In order to better understand the collected experimental data, we have employed the theoretical tool of dimensional analysis, showing that the compressibility of unvulcanized rubber is of great importance for the die swell. Surprisingly, the temperature dependence of the die swell turns out to be much less prominent than standardly assumed. Further key factors influencing the die swell concern the geometries of the die and of the canal. Highlights: New extrusion test modalities are presented. Dimensional analysis is proposed as theoretical concept for analysis of extrusion tests. Temperature turns out as less influential for rubber compressibility and viscosity than expected. The importance of the rubber compressibility for its extrusion behavior is corroborated.